Consciousness and modern culture the emerging new culture [videorecording]. (Oakland, Calif. Spectrum Foundation, 1987)
Summary: Discussion of the new holistic culture that emerged in the late twentieth century. Capra argues that the biological sciences, quantum physics and systems theory will provide a theoritical foundation which will supersede the decaying culture based on a linear, mechanistic worldview.
Credits: guest, Fritjof Capra
Keywords: Culture; Civilization; Consciousness